Postoperative analgesic effect of bupivacaine infiltration following lumbar disc surgery - Tunçkale, Tamer; Karaarslan, Numan; Tunçkale, Melek; Çalışkan, Tezcan (The European Research Journal, 2019)
Objectives: Effectiveness of 0.5% bupivacaine administered onto dura, under lumbar superficial fascia and subcutaneous tissue on postoperative pain control was analyzed in patients undergoing lumbar microdiscectomy. Methods: Sixty adult patients scheduled to undergo elective, single-level lumbar discectomy were randomly divided into four groups: the control group (Control), the subcutaneous tissue group (Group C), which received 20 ml of 0.5% bupivacaine in the subcutaenous tissue, the superficial fascia group (Group F), which received 12 ml bupivacaine in the subcutaneous tissue and 8 ml in the space below the lumbar superficial fascia, and the dura group (Group D), which received a total of 20 ml (100 mg) of bupivacaine, consisting of 10 ml in the subcutaneous tissue, 8 ml in the space below the lumbar superficial fascia, and 2 ml on the dura. Visual Analog Scale Values (VAS) on postoperative 0, 15, 30, 45 minutes, at 1, 2, 4, 6, 12 and 24th hour and time of the first analgesic need were evaluated for all patients and recorded. Results: While mean VAS value measured at min 0 (as soon as the patient awakened) was 2.3 ± 1.2 in Group D; it was 2.7 ± 0.9 in Group C; 2.7 ± 1.0 in Group F and 3.1 ± 0.6 in control group (p = 0.232). At the end of 1th hour, mean VAS value was recorded as 2.8 ± 1.0 in Group D; 3.6 ± 1.5 in Group C; 3.6 ± 1.1 in Group F and 4.4 ± 1.1 in control group (p = 0.005). In Group D, 0.5% bupivacaine administered as 2, 8, 10 ml onto dura, fascia and subcutaneously was detected to provide significantly lower VAS values and significantly longer first analgesic need time. Conclusions: 0.5% bupivacaine administered onto dura, under lumbar superficial fascia and in subcutaneous tissue was detected to be a simple, effective and safe method in lumbar microdiscectomy operations.